SEMG amplitude of the erector spinae in children with scoliotic lesions - Wilczyński, Jacek; Karolak, Przemysław; Janecka, Sylwia; Kabała, Magdalena; Habik-Tatarowska, Natalia; Wypych, Żaneta (Journal of Education, Health and Sport, 2018)
The aim of the study was to analyze the amplitude of SEMG rectifier spine in children with scoliotic changes. SEMG amplitude rectifier back of the camera has been studied Noraxon TeleMyo DTS. The shape of the spine was estimated optoelectronic method Diers formetric III 4D. The research was Carried out in the Posturology Laboratory at the Faculty of Medicine and Health Sciences, UJK in Kielce (Poland). In the group of children with scoliosis curvature of the most frequently occurred on the location of the rib. In girls, it represented (62%) in boys (56%). Univariate analysis of variance showed significant differences among boys in intra-amplitude measurements SEMG variable lower limbs up the left side of the lumbar. Means, that the value of the amplitude distribution SEMG rectifier ridge in the study of lower limbs up the left side of the lumbar differed significantly between the groups scoliotic attitudes, scoliosis and normal. The amplitude of SEMG rectifier ridge in the study of lower limbs up the lumbar left was the lowest in the group of scoliosis. Due to the fact that a group of boys with scoliosis had most of the left-hand direction of curvature in the lumbar region, we can conclude that the greater the amplitude of SEMG rectifier occurred at the back of the concave side of the curvature of the lumbar spine.